Time-resolved investigation of nanometric cell membrane patches with a mid-infrared laser microscope - Intze, Antonia; Temperini, Maria Eleonora; Baldassarre, Leonetta; Giliberti, Valeria; Ortolani, Michele; Polito, Raffaella (Frontiers in Photonics, 2023)
The proton pump Bacteriorhodopsin (BR) undergoes repeated photocycles including reversible conformational changes upon visible light illumination. Exploiting the sensitivity of infrared (IR) spectra to the conformation, we have determined the reaction kinetic parameters of the conductive intermediate M for the wild-type protein and for its slow mutant D96N during its photocycle. Time-resolved IR micro-spectroscopy using an in-house developed confocal laser microscope operating in the mid-IR is employed to record absorption changes of 10-4 at wavelengths λ1 = 6.08 μm and λ2 = 6.35 μm, assigned to backbone and retinal structural modifications, respectively. Protein samples were embedded in dried lipid bilayers deposited on ultraflat gold supports to enhance the surface field. The signals were analyzed according to a simplified photocycle model with only two dominant states: the dark-adapted state BR* and the intermediate M. We obtained the excitation and relaxation times of the intermediate M from exponential fits to the absorption change time traces. Our results constitute a first step towards future plasmonic-assisted nanoscale time-resolved mid-IR spectrometers for the characterization of bioelectronic and light-harvesting nanodevices based on BR.